P106 Potentially missed cancer at endoscopy in Barrett's oesophagus: a national study of rate and associated factors. (19th June 2022) - Kamran, Umair; Evison, Felicity; Rutter, Matt; Adderley, Nicola; Brookes, Matthew; Morris, Eva; Burr, Nick; Valori, Roland; McCord, Mimi; Trudgill, Nigel
Abstract : Background and Aim: Potentially missed or post endoscopy upper gastrointestinal cancer (PEUGIC) is UGI cancer (UGIC) diagnosed within 6 to 36 months of an endoscopy without a cancer diagnosis. We examined the PEUGIC rate among patients with Barrett's oesophagus in England and associated factors. Methods: Using linked National Cancer Registration and Analysis Service and Hospital Episode Statistics databases, all patients diagnosed with UGIC between 2012-2018 who had undergone an endoscopy within 3 years prior to UGIC diagnosis, and a previous ICD10 coding for Barrett's oesophagus (K22.7) were identified. Multivariable logistic regression analysis explored factors associated with PEUGIC in Barrett's oesophagus. Funnel plot with superimposed control limits representing two and three standard deviations from the mean was produced to assess variations in Barrett's PEUGIC rates between trusts. Results: 12, 231 UGIC in patients with Barrett's oesophagus studied. UGIC in patients with Barrett's were diagnosed at an earlier stage (I&II) compared to UGIC patients without Barrett's (40% vs 20% p<0.001) and more were likely to undergo curative endoscopic or surgical resection (47.6% vs 20.5% p<0.001). The PEUGIC rate in patients with Barrett's was 21 (95% CI 20.3-22)% compared to 6.2 (6.1-6.4)% in patients without Barrett's oesophagus, and remained unchanged over the study period. There was significant variation in the Barrett's PEUGIC rate between trusts (7.6% to 39.1%). Figure 1 Funnel plot representing variation in Barrett's PEUGIC rates among NHS trusts. Purple dots represent NHS trusts, green dots represent private providers. Younger age (aged ≤60 odds ratio 2.08 (95% CI 1.78-2.43), compared to ≥80), females (1.22 (1.09-1.36)), increasing comorbidities (Charlson comorbidity score ≥5 2.83 (2.15-3.72), cancer in upper third of oesophagus (1.66 (1.22-2.27)) and providers with high post colonoscopy colorectal cancer rates (1.15 (1.01-1.30)) were positively associated with Barrett's PEUGIC. Oesophago-gastric cancer surgical resection sites had lower PEUGIC rates (0.90 (0.82-0.99). Conclusion: Substantial variation in Barrett's PEUGIC rates among NHS trusts highlights potential variation in the quality-of-care Barrett's patients receive and the need for better adherence to quality standards such as dedicated Barrett's surveillance lists and endoscopists.